2014
DOI: 10.4103/2152-7806.142321
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cerebellar hemangioblastoma in two patients without von Hippel-Lindau disease

Abstract: Background:Two patients who had received a total resection of cerebellar hemangioblastoma developed cerebrospinal fluid dissemination during a long-term follow-up period. We present this rare disease with discussion based on the literature.Case Description:The patients were two women aged 45 and 57 years. In the cerebellar hemisphere, one patient had cystic hemangioblastoma of mural nodule type and the other had solid type. Both the patients successfully underwent total resection by craniotomy. They presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Indeed, none of our patients developed disseminated HB in the absence of previous surgery. An assessment of the tumor cell burden required for dissemination found that a smaller, rather than a larger, number of tumor cells implant at some locations, resulting in subsequent proliferation and the formation of extensive foci [1]. However, we do not know the reason why there was no local recurrence during a relatively short period in any of the presented sporadic HBs patients in our literature, but only distant leptomeningeal seeding.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, none of our patients developed disseminated HB in the absence of previous surgery. An assessment of the tumor cell burden required for dissemination found that a smaller, rather than a larger, number of tumor cells implant at some locations, resulting in subsequent proliferation and the formation of extensive foci [1]. However, we do not know the reason why there was no local recurrence during a relatively short period in any of the presented sporadic HBs patients in our literature, but only distant leptomeningeal seeding.…”
Section: Discussionmentioning
confidence: 92%
“…The most common cause of death in patients with CNS hemangioblastomatosis is respiratory failure, caused by pontomedullary or cervical cord compression [1,18]. Most patients died within 6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer than 20 individual cases of disseminated disease are reported in the literature [4-6, [13][14][15][16][17][18][19][20][21]. The most typical scenario entails discovery of a relatively small number of tumor deposits along the brain stem and spinal cord, generally years after initial diagnosis and/or treatment of a cerebellar hemangioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms underlying tumor spread suggests a small number of cells implant at distant sites giving rise to new tumor lesions. [ 1 ] Craniospinal radiation is recommended for cases of CSF dissemination combined with ventriculoperitoneal shunt depending on other symptoms. Time elapsed between initial surgery and detection of tumor spread was on average 10 years.…”
Section: Discussionmentioning
confidence: 99%